2017
DOI: 10.1590/s1806-37562016000000323
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of closed pleural biopsy in the diagnosis of malignant pleural effusion

Abstract: Objective:Previous studies have demonstrated that closed pleural biopsy (CPB) has a sensitivity of less than 60% for diagnosing malignancy. Therefore, controversy has recently emerged regarding the value of CPB as a diagnostic test. Our objective was to assess the accuracy of CPB in diagnosing malignancy in patients with pleural effusion. Methods:This was a prospective 8-year study of individuals who underwent CPB to establish the etiology of pleural effusion. Information on each patient was obtained from anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The search and selection flow diagram of studies on CPB and MT are shown in Figures 1 and 2, respectively. For CPB, our initial database search yielded a total of 446 citations (Figure 1) from which 10 studies on CPB ultimately met our inclusion criteria and were selected for meta-analysis (2,7,(12)(13)(14)(15)(16)(17)(18)(19); for MT, our initial database search yielded a total of 571 citations (Figure 2) from which 23 studies on MT ultimately met our inclusion criteria and were selected for meta-analysis (1,8,. Tables 1 and 2 show the basic features of the studies selected for analysis as well as their QUADAS scores.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…The search and selection flow diagram of studies on CPB and MT are shown in Figures 1 and 2, respectively. For CPB, our initial database search yielded a total of 446 citations (Figure 1) from which 10 studies on CPB ultimately met our inclusion criteria and were selected for meta-analysis (2,7,(12)(13)(14)(15)(16)(17)(18)(19); for MT, our initial database search yielded a total of 571 citations (Figure 2) from which 23 studies on MT ultimately met our inclusion criteria and were selected for meta-analysis (1,8,. Tables 1 and 2 show the basic features of the studies selected for analysis as well as their QUADAS scores.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Nonspecific inflammation with varying degrees of fibrosis or normal pleura was found in 68% in one study (18). Several studies have highlighted the accuracy of needle biopsy in the diagnosis of malignant pleural effusion (2,5,26). The accuracy of needle biopsy in malignant pleural effusion was estimated to be high by this study because a large proportion were histological confirmed, and repeat biopsy is emphasized which increased the diagnostic contribution above all in malignant tumors.…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports have suggested that the NPVs and −LRs of the needle biopsies are not reliable. 30 In our 2 previous randomized trials, the results were pooled according to the biopsy method used; the diagnostic sensitivity, specificity, PPV and NPV, and −LR are shown in the Table 5. 9,10 Patients were randomized to CT-ANPB versus MT, CT-ANPB versus US-CNPB, irrespective of CT findings in these studies.…”
Section: Discussionmentioning
confidence: 99%